Christian Bobin or non-literature - Montiel López, Jesús (Razón y fe, 2019)
Using literary language, the poet Christian Bobin proposes on his books a displacement from costume to celebration. This rhetoric model reflects a literary discourse with two very different parts: On the one hand, a trivial event; and on the other hand, through a vision or an epiphany, an invisible and transfiguring reality that brings us back to a conciliation with custom. This essay has two main goals: Firstly, it aims at claiming Christian Bobin´s work, which has been neglected by academic researchers; but it also intends to offer a definition of non-literature or literature as a healing instrument.
Keywords: Christian Bobin; language; literature; poetry; transcendence; spirit